Theoretical investigation on the mechanism of NO3 radical-initiated atmospheric reactions of phenanthrene - Zhao, Nan; Shi, Xiangli; Xu, Fei; Zhang, Qingzhu; Wang, Wenxing (Journal of molecular structure, 2017)
Phenanthrene is a polycyclic aromatic hydrocarbon from fossil fuel combustion with toxic properties. The products arising from atmospheric reaction can be more mutagenic and carcinogenic compared to unmodified phenanthrene, and are therefore important to be studied. The products of the specific NO3-radical reactions with phenanthrene where therefore investigated in this study by means of Density Functional Theory (DFT). The results show that the main products are proposed to be 10-(nitrooxy)-10-hydro-phenanthrene-9-one, 2,2′-diformylbiphenyl, 9,10-phenanthrenequinone, 9-fluorenone and dibenzopyranone. 10-(nitrooxy)-10-hydro-phenanthrene-9-one and 2,2′-diformylbiphenyl are classified as first-generation products which are subject to secondary reactions to produce 9,10-phenanthrenequinone, 9-fluorenone and dibenzopyranone. The rate constants of elementary reactions were assessed by Rice-Ramsperger-Kassel-Marcus (RRKM) theory. The atmospheric lifetime of Phe determined by the gas-phase reaction with NO3 is estimated to be 1.8 h, based on the calculated overall rate constant of 3.04 × 10−13 cm3 molecule−1 s−1 at 298 K and 1 atm. Combined with available experimental observation, this work should help to clarify the transformation and potential health risk of Phe in the atmosphere. •The mechanism of NO3-initiated atmospheric reactions of Phe was investigated by DFT.•Phe-NO3 reactions are mainly initiated through NO3 addition to 9,10-bond of Phe.•The sequential reactions of NO3-Phe adduct isomers are O2 addition reactions.•9,10-phenanthrenequinone and two ketones are produced in secondary reactions.•The atmospheric lifetime of Phe by reaction with NO3 is estimated to be 1.8 h.